2017
DOI: 10.1053/j.ajkd.2016.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Diuretic Resistance

Abstract: Diuretic resistance is defined as a failure to achieve the therapeutically desired reduction in edema despite a full dose of diuretic. The causes of diuretic resistance include poor adherence to drug therapy or dietary sodium restriction, pharmacokinetic issues, and compensatory increases in sodium reabsorption in nephron sites that are not blocked by the diuretic. To illustrate the pathophysiology and management of diuretic resistance, we describe a patient with nephrotic syndrome. This patient presented with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
80
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 49 publications
1
80
0
1
Order By: Relevance
“…Generalized edema is an essential clinical feature of NS independent of various underlying etiologies. Two major hypotheses have been proposed to explain edema formation, the underfill and overfill theory, respectively, which have been recently reviewed (Ellis ; Hoorn and Ellison ; Ray et al. ; Teoh et al.…”
Section: Introductionmentioning
confidence: 99%
“…Generalized edema is an essential clinical feature of NS independent of various underlying etiologies. Two major hypotheses have been proposed to explain edema formation, the underfill and overfill theory, respectively, which have been recently reviewed (Ellis ; Hoorn and Ellison ; Ray et al. ; Teoh et al.…”
Section: Introductionmentioning
confidence: 99%
“…The selective uPA‐neutralizing antibody treatment showed a minor and late difference in accumulated Na‐balance, which is likely why weight change was borderline significant. Irrespective of the observed differences and possible explanations, both studies suggest that blocking ENaC function is an appropriate target for the treatment of sodium and fluid retention in NS, which is supported by recent case reports . An ongoing, randomized clinical trial is currently exploring the effect of amiloride in paediatric patients with NS .…”
mentioning
confidence: 69%
“…Contrary to the classical view of altered fluid distribution second to a low plasma oncotic pressure, accumulating evidence suggest that oedema formation in NS is because of the aberrant renal sodium retention . It has been shown that pharmacologic blockade of the epithelial sodium channel (ENaC) using amiloride can prevent sodium retention and relieve nephrotic oedema in both rats, mice and humans . As aldosterone is typically in normal range or suppressed in NS, possibly after a variable and short initial increase, the question is what activates ENaC in NS?…”
mentioning
confidence: 97%
“…Second, it is common for clinicians to use multiple diuretics to deal with diuretic resistance. 5,17) Third, since torsemide is more expensive than furosemide in China, combination treatment may reduce the cost for HF patients compared with torsemide and have potential benefits compared with furosemide. It is noteworthy that we assessed the associations between combination treat-LOOP DIURETIC IN CHRONIC HEART FAILURE ment and one-year all-cause and CV mortality compared with furosemide for the first time.…”
Section: 7)mentioning
confidence: 99%